The Relationship Of Patients' Knowledge About Atibiotics And Compliance With Atibiotic Use In Narumonda Health Center - Baharuddin J.E.A. Togatorop; Meliani Dwi Lestari; Gaberiela S.Y. Simangunsong; Elisabeth T. Siahaan (International Journal of Health Engineering and Technology, 2023)
Antibiotics have been proven to be beneficial for human life since they were first discovered until now. However, improper use can cause various problems. The most important problem is the emergence of bacterial strains resistant to various types of antibiotics. One of the factors that supports this phenomenon is the patient's lack of knowledge and understanding about antibiotics. Lack of knowledge will influence patient non-compliance in using antibiotics. This study aims to determine the relationship between patient knowledge about antibiotics and compliance with antibiotic use at the Narumonda Community Health Center, Toba Regency in 2023. This type of research is descriptive and carried out prospectively. Data were collected using a questionnaire from 35 respondents. The research results showed that 60% of respondents had good knowledge, 17.14% had sufficient knowledge and 22.86% had poor knowledge. The majority of respondents (82.86%) did not comply with the use of antibiotics and only 17.14% of respondents complied with the use of antibiotics. A relationship was found between knowledge and compliance with the results of statistical tests (Spearman correlation test) with a value of p < 0.05. The correlation coefficient value is 0.360 with a positive correlation direction, meaning that there is a correlation that is meaningful and in the same direction but has a weak relationship